Super memory [compact disc] : speed read, recall names, and learn faster. - Small, Gary, 1951-; Tracy, Brian; Iverson, Larry (Made for Success collection., 2011)
Learn how to recall names, faces, and crucial facts easily as you tap your enormous capacity to remember information. Combine speed reading skills with memory techniques from a two-time USA Memory Champion for memorizing information and you have an unprecedented resource for learning in the twenty-first century.